2020
DOI: 10.3390/cancers12041005
|View full text |Cite
|
Sign up to set email alerts
|

Dysmetabolic Circulating Tumor Cells Are Prognostic in Metastatic Breast Cancer

Abstract: Circulating tumor cells (CTCs) belong to a heterogeneous pool of rare cells, and a unequivocal phenotypic definition of CTC is lacking. Here, we present a definition of metabolically-altered CTC (MBA-CTCs) as CD45-negative cells with an increased extracellular acidification rate, detected with a single-cell droplet microfluidic technique. We tested the prognostic value of MBA-CTCs in 31 metastatic breast cancer patients before starting a new systemic therapy (T0) and 3–4 weeks after (T1), comparing results wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The study was conducted at the IRCCS-CRO Aviano-National Cancer Institute and approved by the Institutional Review Board with number IRB-12-2014 ( 32 ). Informed and written consent was obtained from all patients and healthy donors before their enrolment, and their clinico-pathological information was recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was conducted at the IRCCS-CRO Aviano-National Cancer Institute and approved by the Institutional Review Board with number IRB-12-2014 ( 32 ). Informed and written consent was obtained from all patients and healthy donors before their enrolment, and their clinico-pathological information was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the procedure employed for the enrichment and identification of CTCs with a metabolism-based assay (MBA) has been published previously ( 32 ). Briefly, peripheral blood samples (2.5 ml) were drawn into K2-EDTA Vacutainer tubes (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified 16 studies that assessed the presence of CTCs and their use as predictive biomarkers for treatment response or relapse. These studies associated a high CTC count with shorter progression-free survival (PFS), DFS and/or OS [ 79 , 80 , 81 , 82 , 83 , 84 ], resistance to different therapies [ 80 , 84 , 85 ], worse outcome [ 82 , 84 , 85 ], disease relapse [ 82 , 85 ], and metastasis [ 86 ]. Some studies have also evaluated CTC counts with different phenotypes, such as mesenchymal CTCs (mCTCs) and epithelial CTCs (eCTCs).…”
Section: Prediction Of Treatment Response and Early Detection Of Relapsementioning
confidence: 99%
“…Coherently, the upregulation of the same gene represents an efficient strategy to identify metastatic prostate cancer patients [188]. The high glycolytic metabolism has also been proven to result into a high lactate production, which was indeed used in devices aimed at CTC isolation [189,190]. Ultimately, a work from Aceto and colleagues conducted in CTCs derived from breast cancer patients pointed out a significant hyperactivation of the ATP metabolic process and amino acid metabolism [191].…”
Section: Metabolic Requirements Of Circulating Tumor Cellsmentioning
confidence: 99%